Online searching in PTAR Puncak Perdana / Mohd Fadlli A. Rahim - A. Rahim, Mohd Fadlli (Faculty of Information Management, 2008)
This study was undertaken to determine the Online Searching in PTAR Puncak Perdana. The overall purpose of the study was To discover the effectiveness on using online databases, To identify problems that users faced while using online databases and To identify on the awareness level of library users on online databases provided in the library. The method that been use for this study is distribution of questionnaire to sample among the group of students in UiTM Campus Puncak Perdana. 100 sets of questionnaires would be distributed to the five different faculties that are Faculty of Information Management, Faculty of Mass communication and Media, Faculty of Technology Creative and Artistic, Faculty of Accountancy, and Academy of Language Studies. The contents have been organized five parts. The first part is to analyze the background of students. The second part focuses on the effectiveness of online searching. The third parts focus on the problems on online searching. The fourth part focuses the awareness of online databases by the users. In the last part, is about the suggestions made by users. It will require users to give their opinion on how to improve the online services in the library, especially online databases.